Intraday trading patterns in the equity warrants and equity options markets: Australian evidence - Lydia Segara; Reuben Sagara (Australasian Accounting, Business and Finance Journal, 2007)
This paper extends the microstructure literature, by examining the previously undocumented intraday trading patterns in trading volume, price volatility, order depth and relative spreads for both the warrant and option market in Australia. Comparisons of intraday variations across these derivative securities allows for insight to be drawn into competing market microstructure theories and provides the opportunity to examine whether market design differences explain variations in observed intraday patterns. We find that intraday trading patterns documented in the warrant and option markets can be explained by their market designs, along with theories relating to time-varying information asymmetry and time-varying hedging trades around nontrading periods.
Keywords: Warrants market; Options market; Australian Stock Exchange; Intraday trading behaviour